An Analysis of Perempuan Berkalung Sorban Novel: Feminist Perspective - Aryanika, Septa (English Education: Jurnal Tadris Bahasa Inggris, 2016)
In the patriarchy society, women are viewed to be the second class under  men. This study aims at knowing how feminism in Perempuan Berkalung  Sorban novel by Abidah  El  Khalieqy.  The  purpose  of  this  study  are  to: 1) describe  feminism  in  novel Perempuan Berkalung  Sorban novel, 2) know  the groups of feminism in Perempuan Berkalung Sorban novel. This research was qualitative descriptive research method. The results showed: 1) the feminism in  Perempuan Berkalung Sorban novel describe a woman’ stuggle in getting her existence and rights as a independent human being, and 2) this novel contents liberal feminism and radical feminism.